2021
DOI: 10.1002/bab.2233
|View full text |Cite
|
Sign up to set email alerts
|

Caspase‐3: Structure, function, and biotechnological aspects

Abstract: Caspase‐3, a cysteine‐aspartic acid protease, has recently attracted much attention because of its incredible roles in tissue differentiation, regeneration, and neural development. This enzyme is a key zymogen in cell apoptosis and is not activated until it is cleaved by initiator caspases during apoptotic flux. Since caspase‐3 has represented valuable capabilities in the field of medical research, biotechnological aspects of this enzyme, including the production of recombinant type, protein engineering, and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
109
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(132 citation statements)
references
References 90 publications
1
109
0
1
Order By: Relevance
“…Based on our results of TEM and ERG, we expected to see reduced apoptosis in the WIF1‐treated OIR mice retina. Figure 7A showed that WIF1 overexpression strongly suppressed the levels of caspase‐3 and cleaved capsase‐3, which suggested reduced retinal apoptosis 27 . In addition, we employed Terminal deoxynucleotidyl transferase (TdT) dUTP Nick‐End Labeling (TUNEL) staining to evaluate apoptosis in retinal cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our results of TEM and ERG, we expected to see reduced apoptosis in the WIF1‐treated OIR mice retina. Figure 7A showed that WIF1 overexpression strongly suppressed the levels of caspase‐3 and cleaved capsase‐3, which suggested reduced retinal apoptosis 27 . In addition, we employed Terminal deoxynucleotidyl transferase (TdT) dUTP Nick‐End Labeling (TUNEL) staining to evaluate apoptosis in retinal cells.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 7A showed that WIF1 overexpression strongly suppressed the levels of caspase-3 and cleaved capsase-3, which suggested reduced retinal apoptosis. 27 In addition, we employed Terminal deoxynucleotidyl transferase (TdT) dUTP Nick-End Labeling (TUNEL) staining to evaluate apoptosis in retinal cells. We revealed a 75% decreased in apoptotic nuclei in the retina of LV-WIF1-treated OIR retina, compared to controls (Figure 7B).…”
Section: Wif1 Decreased Hypoxia-driven Photoreceptor Apoptosis By Red...mentioning
confidence: 99%
“…These data indicate that PI3Kγ deficiency inhibits apoptotic cell death in the kidney following IRI. Caspase 3 is the final effector caspase that results in apoptotic cell death [ 23 , 24 ]. Therefore, the effect of PI3Kγ deficiency on caspase 3 protein expression was examined in the kidney.…”
Section: Resultsmentioning
confidence: 99%
“…Remarkably, the glutathione S-transferase activity in the anterior portion of P. lividus intestine has been employed as biomarker of environmental contamination, revealing an important role in the homeostasis of this tissue [69]. Finally, CASP3 gene encodes for a cysteine-aspartic acid protease (caspase) that has a crucial role in the execution-phase of apoptosis [70]. This protein has been described as an essential element if the innate immunity of sea urchins [64].…”
Section: Discussionmentioning
confidence: 99%